2022
DOI: 10.26434/chemrxiv-2022-6s4zj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cobalt/Salox-Catalyzed Enantioselective Dehydrogenative C–H Alkoxylation and Amination

Abstract: The past decade has witnessed a rapid progress in asymmetric C–H activation. However, the enantioselective C–H alkoxylation and amination with alcohols and free amines remains elusive. Herein, we disclose the first enantioselective dehydrogenative C–H alkoxylation and amination enabled by a simple cobalt/salicyloxazoline (Salox) catalysis. The use of cheap and readily available cobalt(II) salts as catalysts and Saloxs as chiral ligands provides an efficient method to access P-stereogenic compounds in excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…According to recent data, osimertinib, a third-generation inhibitor used to treat non-small cell lung cancer, including those with brain metastases, has a better ability to penetrate through the BBB [34]. A recent study on xenografts from patients with glioblastoma [35] showed the efficacy of osimertinib in controlling cell growth even with no EGFR expression. This, together with data on ability to effectively overcome the BBB, makes osimertinib a promising drug for treatment.…”
Section: Inhibitors Of Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…According to recent data, osimertinib, a third-generation inhibitor used to treat non-small cell lung cancer, including those with brain metastases, has a better ability to penetrate through the BBB [34]. A recent study on xenografts from patients with glioblastoma [35] showed the efficacy of osimertinib in controlling cell growth even with no EGFR expression. This, together with data on ability to effectively overcome the BBB, makes osimertinib a promising drug for treatment.…”
Section: Inhibitors Of Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…Many diabetic people experience diabetic neuropathy (DN), a frequent and crippling consequence of diabetes. In addition to hyperglycemia, the pathogenesis of DN includes intricate and multiple mechanisms that involve critical intracellular pathways, proinflammatory cytokines, neurons and satellite glial cells (Bishnoi et al, 2011;Jia et al, 2017;Cheng et al, 2021;Chen et al, 2022). This editorial synthesizes insights from four pioneering studies in 2023 that shed new light on the understanding and management of DN.…”
mentioning
confidence: 99%